PENGGUNAAN AUDIO VISUAL DALAM PEMBELAJARAN KEMAHIRAN BERBICARA BAHASA ARAB BAGI MAHASISWA UNIVERSITAS AL-AZHAR INDONESIA - Vina Amalia Putri; Faisal Hendra (Penerbit Lafadz Jaya, 2023)
Arabic is one of the foreign language courses that must be taught at Al-Azhar Indonesia University (UAI) as a compulsory subject. Arabic is a characteristic of the UAI campus and is one of its superior characteristics, namely a special course that other public universities do not have. . The use of Arabic in the study program, Faculty of Arabic Language, Al-Azhar University Indonesia began in early 2000. All teachers on the Al-Azhar University Indonesia campus still feel that there is a failure in the level of success of the material that has been taught, one of which is Arabic speaking proficiency which is highly expected. Learning objectives for Arabic speaking proficiency, teaching materials from language proficiency courses, application of language proficiency teaching methodology, lecturers teaching Arabic speaking proficiency courses in the eyes of students and students' perceptions of evaluation techniques used by lecturers teaching language speaking proficiency courses in the program Arabic Literature Studies, Al-Azhar University Indonesia.